2018
DOI: 10.1159/000490800
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Diabetes-Related Changes in the Free Fatty Acid Composition of the Human Stratum Corneum

Abstract: Of particular importance for Stratum corneum (SC) lipids are the free fatty acids (FFAs). Age-related changes of the SC structure lead to diminished capacity for barrier compensation. The aims of this cross-sectional study were to identify even-numbered especially odd-numbered FFAs within the intercorneocytic lamellar lipid structures of the SC and to explore age- and diabetes-related changes in FFAs. Gas chromatography – flame ionisation detection was used to qualitatively and quantitatively assess FFAs extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
1
5
0
1
Order By: Relevance
“…It has been found that the fatty acid composition of serum lipids and skeletal muscle phospholipids can affect insulin sensitivity in elderly diabetic patients, which further confirms the relationship between lipid metabolism and type 2 diabetes mellitus. 94 In our investigation, HQLYD had an intense influence on glycerophospholipids, such as PC and PE, which were observably elevated in the model rats. PC and PE as the glycerophospholipids with the highest contents in mammals are vital elements in biomemebranes and transport the majority of membrane lipids within cells.…”
Section: Discussionsupporting
confidence: 45%
“…It has been found that the fatty acid composition of serum lipids and skeletal muscle phospholipids can affect insulin sensitivity in elderly diabetic patients, which further confirms the relationship between lipid metabolism and type 2 diabetes mellitus. 94 In our investigation, HQLYD had an intense influence on glycerophospholipids, such as PC and PE, which were observably elevated in the model rats. PC and PE as the glycerophospholipids with the highest contents in mammals are vital elements in biomemebranes and transport the majority of membrane lipids within cells.…”
Section: Discussionsupporting
confidence: 45%
“…epidermis, dermis, and hypodermis [2], and the skin barrier function is mostly ensured by the stratum corneum (SC), the uppermost layer of the epidermis [3][4][5][6]. The SC consists of 10−20 layers of corneocytes, which are enucleated flattened cells embedded in lipid lamellar regions [7][8][9]. The SC thickness is determined as the distance from the skin surface to the boundary between the SC and the stratum granulosum (SG) [10]; it varies according to the area and individual.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, aunque la xerosis no sea clínicamente evidente, el proceso natural de recambio epidérmico está alterado (6) . También se ha documentado una menor actividad de las glándulas sebáceas (11) y un desequilibrio en la composición de los lípidos del estrato córneo, dado por la reducción en los niveles de los ácidos grasos libres (12) . Por lo tanto, las anormalidades que se presentan en la función de la barrera de la piel de los diabéticos podrían ser consecuencia de su fragilidad estructural y del desarrollo defectuoso de sus células epidérmicas.…”
Section: Fisiopatologíaunclassified